Biomedical engineering systems and technologies : 9th International Joint Conference, BIOSTEC 2016, Rome, Italy, February 21-23, 2016, Revised selected papers /: 9th International Joint Conference, BIOSTEC 2016, Rome, Italy, February 21-23, 2016, Revised selected papers. (2017) - Unknown
No abstract available